Inducement of semitendinosus tendon regeneration to the pes anserinus after its harvest for anterior cruciate ligament reconstruction-A new inducer grafting technique - Murakami Hidetaka; Soejima Takashi; Inoue Takashi; Kanazawa Tomonoshin; Noguchi Kouji; Katouda Michihiro; Tabuchi Kousuke; Noyama Megumi; Yasunaga Hideki; Nagata Kensei (BMC, 2012)
Abstract Purpose To investigate the usefulness of the "inducer grafting" technique for regeneration of the semitendinosus (ST) tendon after its harvest for anterior cruciate ligament (ACL) reconstruction. Methods Twenty knees of 20 patients (mean age at the time of surgery, 23.1 years) underwent ACL reconstruction with a double bundle autograft using the ST tendon (7 patients) and the ST + the gracilis (G) tendons (13 patients). "Inducer grafting" technique After harvesting the ST tendon, a passing pin with a loop thread is inserted along with the tendon stripper. The passing pin is pulled out from the medial thigh and the loop thread retained. As an inducer graft, the ST tendon branch is used. After the ACL graft has been secured, the inducer graft is sutured to the pes anserinus and the proximal end passed through by pulling the thread out. Then the inducer graft is placed within the tendon canal. The mean follow-up period was 15 months. The presence and morphology of the regenerated ST tendon were examined by MRI. And the isometric hamstring strength was examined at 45°, 90° and 120° of knee flexion. Results One month after the operation in all the patients, MRI demonstrated a low-intensity structure at the anatomical location of the ST, at the level of the superior pole of the patella and the joint line, apparently representing the regenerated ST tendon. Four months after the operation, the distal portion of the regenerated ST tendon had reached the pes anserinus in all patients. Twelve months after the operation, the regenerated ST tendon was hypertrophic in 19 of the 20 patients (95%). The isometric knee flexion torque of the ACL-reconstructed limb was significantly lower at 90° and 120° compared with the contralateral limb. Conclusion These results suggest that the "inducer grafting" technique is able to improve the regeneration rate of the harvested ST tendon and promote hypertrophy of the regenerated ST tendon, extending all the way to the pes anserinus. However, this technique couldn't improve the deficits in knee flexion torque after ACL reconstruction.